Raise the roof mapping and characterizing the transformations of the Ifugao Bale in the Batad Rice Terraces - Belga, Marie Edraline B. (2023)
Access online through this link: https://journals.upd.edu.ph/index.php/muhon/article/view/9534/8414
Keywords: Batad (Ifugao); Geographic Information Systems